y'' + y ‘+2x= 0

数学 | 大学数学41閲覧xmlns="http://www.w3.org/2000/svg">50

ベストアンサー

0

その他の回答(2件)

0

y''+y'+2x=0、(先ず x で積分) y'+y=aーx^2、(一階線形, 積分因子は e^x) (y*e^x)'=(aーx^2)*e^x y*e^x=(Aーx^2+2x)*e^x+B y(x)=Aーx^2+2x+B*e^(-x)、(おしまい)

0

e^xを掛ける (e^x)y'' + (e^x)y ‘+2x(e^x)= 0 ここで、(e^x)y' を微分すると ((e^x)y')'=(e^x)y'' + (e^x)y ‘ だから、前の2項は、(e^x)y'の微分同じ よって ((e^x)y')'+2x(e^x)=0 ((e^x)y')'=ー2x(e^x) 積分すると (e^x)y'=-2∫x(e^x)dx (e^x)y'=-2x(e^x)+2∫(e^x)dx y'=-2x(e^x)+2e^x+C (C積分定数) y'=-2x+2+Ce^(-x) 積分する y=-x^2+2x-Ce^(-x) + C2 (C2積分定数) -C=A,C2=B (A,B定数)とおいて y=-x^2+2x+Ae^(-x) + B